Welcome to Thyroid Research - Lewinski Andrzej; Köhrle Josef; Alevizaki Maria; Jarzab Barbara (Thyroid Research, 2008)
Abstract Welcome to the first issue of Thyroid Research, a new journal published by BioMed Central, which aims at providing a platform for both researchers and clinicians to discuss a broad spectrum of thyroidology and related issues. These include physiological mechanisms of thyroid hormone action, secretory regulations, immunological and genetic aspects and, finally, news and information on state-of-the-art diagnostic equipment and treatment protocols for more effective management of thyroid disorders.